High rate lithium slurry flow batteries enabled by an ionic exchange Nafion composite membrane incorporated with LLZTO fillers. (April 2023) - Wang, Ruji; Yang, Lipeng; Li, Jin; Pan, Shanshan; Zhang, Fengjie; Zhang, Haitao; Zhang, Suojiang
Abstract: Lithium slurry flow batteries (LSFBs) possessing decoupled energy/power density feature and high energy density are considered as the most promising next-generation energy storage devices. However, their cycling stability is depressed by the high permeability of active components through porous separator and low conductivity of lithium ion in non-porous membrane. Herein, a novel Nafion/PVDF/LLZTO ion exchange membrane (IEM) with high ion conductivity and mechanical properties is proposed. As-optimized IEM possesses an ionic conductivity of 0.29 mS cm −1 . Both experimental and density functional theory (DFT) calculation studies suggest that the complementary effect between inorganic ceramic fillers LLZTO and polymer materials favor the generation of new Li + migration expressway and dehydrofluorination. The H-bonding interactions can successfully address the poor mechanical strength issues. Moreover, the sandwich-like structure by commercialized PE buffer layer will be beneficial to the improved stability and can effectively suppress the swelling effect of membrane in organic electrolyte. Consequently, LFP//LTO slurry cells containing PE/NPL3/PE membrane exhibit extraordinary performance under 0.3 C. Assembled slurry pouch cells could be cycled stably for more than 270 h at room temperature. This ingenious strategy of introducing inorganic ceramic fillers into the composite membrane will pave a novel promising direction to the development of LSFBs. Graphical Abstract: The poor mechanical and swelling feature in organic electrolytes of Nafion membrane pose a critical challenge for applications in lithium slurry flow batteries. Herein designs a novel ionic exchange Nafion composite membrane to boost ion conductivity, enhance mechanical properties and facilitate Li + migration, enabling extraordinary performance of cells. ga1 Highlights: Lithiated Nafion and inorganic ceramic fillers are firstly used to form membranes for lithium slurry flow batteries. Optimized ionic exchange membrane exhibits excellent ionic conductivity and mechanical properties. The mechanism of improved ionic conductivity introduced LLZTO is unraveled. LFP//LTO slurry batteries exhibit excellent a cycling period of 810 h.